Occupational Air Pollutants and Early Kidney Injury: Insights from Oxidative Stress and KIM-1 Biomonitoring in Iron and Steel Industry Workers. - Mona Abdallah Ramadan; Hebatallah Saad Teleb; Marwa Mohammed Fouad (Journal of Occupational & Environmental Medicine, 2026)
Objectives: The current study aimed to investigate the association between occupational exposure to air pollutants and renal function parameters, as well as oxidative stress. Methods: In a cross-sectional comparative study, 88 participants were grouped into exposed workers and controls. Occupational air pollutant levels, renal function parameters, and oxidative stress markers were evaluated in an iron and steel facility. Results: Although environmental pollutant concentrations were within recommended permissible limits, exposed workers demonstrated significantly elevated serum creatinine, kidney injury molecule-1 (KIM-1), and malondialdehyde (MDA) levels, alongside a significant reduction in eGFR compared to the reference group. In addition, the duration of employment was positively correlated with serum creatinine and MDA while negatively correlated with eGFR. Conclusion: Occupational exposure to air pollutants may adversely affect renal function, even when exposure levels comply with established regulatory standards.